Polymorphisms in lymphotoxin-alpha as the "missing link" in prognosticating favourable response to omega-3 supplementation for dry eye disease: a narrative review - Paik, Benjamin (2023)
Elements of inflammation are found in almost all chronic ocular surface disease, such as dry eye disease. The chronicity of such inflammatory disease speaks to the dysregulation of innate and adaptive immunity. There has been a rising interest in omega-3 fatty acids to attenuate inflammation. While many cell-based (in vitro) studies verify the anti-inflammatory effects of omega-3, different human trials report discordant outcomes after supplementation. This may be due to underlying inter-individual differences in inflammatory cytokine metabolism (such as tumor necrosis factor alpha (TNF-α)), in which genetic differences might play a role, such as polymorphisms in the lymphotoxin alpha (LT-α) gene. Inherent TNF-α production affects omega-3 response and is also associated with LT-α genotype. Therefore, LT-α genotype might predict omega-3 response. Using the NIH dbSNP, we analyzed the relative frequency of LT-α polymorphisms among various ethnicities, each weighted by the genotype's probability of positive response. While the probability of response for unknown LT-α genotypes are 50%, there is greater distinction in response rates between various genotypes. Hence, there is value in genetic testing to prognosticate an individual's response to omega-3.